Xanthation of alginate for heavy metal ions removal. Characterization of xanthate-modified alginates and its metal derivatives - Córdova B.M. (2021)
Xanthates are widely used in mining industry as collectors for its high affinity towards metal sulfides and precious metal ores. The possibility of using alginate for xanthation has not been explored yet despite the feasibility by the presence of hydroxyl groups alongside the polymeric chains. Therefore, this work aims to evaluate the alginate as a matrix for xanthation and its application on heavy metal ions removal. In order to obtain green materials, important pararmeter were explored such as the effect of reaction time (4–12 h), type of base (NaOH/KOH) and amount of carbon disulfide (2–10%v/v). Xanthated alginates were analyzed by NMR techniques and evidence of β-elimination was detected at 5.45 ppm. Furthermore, the presence of S element was confirmed by EDS mapping technique, while XRD showed a semi-crystalline structure. On the other hand, the chemical shifts of δ(C=S) and ν(C=S) bands were found around 863–805 cm−1 and 662–602 cm−1 respectively. Also, a shoulder at 182 ppm is appreciated by NMR in solid state attributed to C[dbnd]S group. According to FESEM analyses, morphology of xanthated alginates is affected by interaction with heavy metal ions. Finally, suitable materials for the removal of heavy metal ions were established at optimum pH values. © 2020